A aplica????o da andragogia na educa????o a dist??ncia pelos profissionais de treinamento e educa????o corporativa - Oliveira, Jackes Teixeira de (2018)
Seventy-eight percent of workers in the Brazilian industry have only a High School diploma. Therefore, organizations need to develop in-house educational actions to reach their goals. According to previous studies, face-to-face training has been slowly replaced by distance learning and professionals who work in corporate education do not have the pedagogical training to ensure their proposals are efficient and effective. Thus, the present study mapped key andragogic processes that must considered by these professionals and inquired whether they have been used in distance learning work routine. The results show that the application of andragogy to distance learning educational actions was a challenge to most interviewees.